Letter : Save the Basque Children Fund - Dukes, Charles
037-0077-001 NATIONAL UNION OF GENERAL & MUNICIPAL WORKERS REGISTERED TRADE UNION No. 1880T. An Approved Society for National Health Insurance CD/AA. Affiliated to: Trades Union Congress, the Labour Party, Confederation of Shipbuilding and Engineering Unions. National Federation of Building Trades Operatives, International Federation of Civil Servants and Employees in Public Services. President Rt. Hon. J.R. Clynes, M.P. Vice-President A. Hayday, M.P. National Officers Rt. Hon. Margaret Bondfield, J.P. J. Jones, M.P. General Secretary CHAS. DUKES Telegraphic Address "UNITUDE WESTCENT LONDON" Telephone EUSTON 3644 (3 lines) National Industrial Officers W. Sherwood, J.P. G.P. Dean H.N. Harrison H. Bullock M. Hewitson, J.P. T. Williamson, J.P National Woman Officer Miss D.M. Elliott, J.P. Private & Confidential Your Ref.: Our Ref.: CD/14. PERSONAL. All communications must be addressed to the General Secretary Head Office: 5 ENDSLEIGH GARDENS LONDON, W.C.1 Mr. H.V. Tewson, Trades Union Congress, Transport House (South Block), Smith Square, S.W.1. 19th July, 1937. Dear Mr. Tewson, "SAVE THE CHILDREN" FUND. Our Southern District just recently sent a cheque for £10. to the above Fund. In remitting this amount to me it was pointed out that some dissatisfaction has arisen in the Southampton area concerning certain changes at the camp wherein the refugee children from Spain have been placed. Without any definite authenticity however we have been informed that the work formerly done on a voluntary basis has now ceased, and that paid persons, with some Government official, are now dealing with this work. In addition, some doubt has been cast upon the administration of the Funds. I would be glad to have your comments on this as I feel sure you will have the facts. Yours sincerely, Chas. Dukes General Secretary. 292/946/37/77